Sistem Pendukung Keputusan Implementasi Penentuan Jurusan Pada SMK 5 Bengkulu Selatan Dengan Menggunakan Metode Weighted Product - Koko, Betri; Siswanto, Siswanto; Supardi, Reno (UNIVED Press, 2024)
In general, prospective new students are confused about choosing an engineering major that suits their abilities, so that in choosing a major they often follow the choice of their closest friends or their parents' choice. Choosing an inappropriate major will have consequences for the future of the new student. For this reason, a prospective new student must know his academic abilities and interests. With the decision support system for determining majors, it is hoped that it can help prospective new students to find out the greatest potential in choosing a major that suits their academic abilities and talents. This Decision Support System uses the Weighted Product method to find out which prospective new students have the potential to enter the engineering major and to find out choose the right major. The weighted product method is a method of determining a decision by multiplying to be able to relate attribute values, where each attribute must first be raised to the power of the weight of the attribute in question.